Fractional Trading - Da, Zhi; Fang, Vivian W; Lin, Wenwei (Review of Financial Studies, 2025)
Abstract Fractional trading (FT)—the ability to trade less than a whole share—removes barriers to high-priced stocks and facilitates entry by capital-constrained retail investors. We observe a surge of tiny trades, measured using off-exchange one-share trades, among high-priced stocks compared to low-priced stocks after FT is introduced to the U.S. equity markets. These tiny trades, when coordinated during attention-grabbing events, are forceful enough to exert large price pressure on high-priced stocks. Further evidence suggests that FT can even fuel meme-stock-like trading frenzies and bubbles in high-priced stocks, for which the feedback effect likely plays a role. (JEL G10, G12, G14, G18, G32, G41)